The Standing Muraja’ah Method in Optimizing Memorization Ability at MIT Tonoboyo Magelang - Baedowi, Kholil; Saril, Mohamad Johan; Abidin, Zaenal (EduLine: Journal of Education and Learning Innovation, 2025)
This research is motivated by the discovery of a unique muroja’ah method that differs from other schools and aims to examine and optimize the memorization abilities of students at MIT Tonoboyo Magelang through the application of this method in tahfizh learning. The objectives of this study are to assess the reading and memorization skills of students at MIT Tonoboyo Magelang, evaluate the methods applied in this learning process, and provide recommendations to enhance students' memorization skills. This research also aims to optimize the abilities to read, memorize, and write the Qur'an by utilizing the muroja’ah method at MIT Tonoboyo Magelang. The focus of this research is on developing students' memorization capabilities and implementing effective methods in tahfizh education. The issues investigated include the level of Qur'an memorization among students, the methods used by teachers in teaching tahfizh, and the challenges faced by students in memorizing the Qur'an. The research method employed is field research, aiming to analyze ways to improve memorization abilities through the implementation of the muroja’ah method. Data were obtained through observations, interviews, and direct practice in the tahfizh learning process at MIT Tonoboyo Magelang. The results of the study indicate that: first, the ability of students at MIT Tonoboyo Magelang to memorize the Qur'an has reached the targets set by the tahfizh teachers; second, although some students struggle with fluency in reciting their memorization, the muroja’ah method can enhance their ability to memorize the Qur'an.